DIMENSI TUBUH SAPI BALI DI UNIT PELAKSANA TEKNIS PEMBIBITAN SAPI BALI SOBANGAN, BADUNG - I W., Bagiarta; Mudita, I M.; Roni, G. K.; Lindawati, S. A. (Jurnal Peternakan Tropika; Vol 5 No 1 (2017), 2017)
A research has been conducted to determine body dimensions of bali cattle in Unit Pelaksana Teknis (UPT) Pembibitan Sapi Bali, Sobangan, Badung for one month from October until November 2016. A total of 288 bali cattle are divided into 8 blocks of cattle shed used in this research. The observed body dimensions are body length, chest circumference, body weight, and body condition score. The Body weight estimation by body dimension and the body condition scores made by direct observation. The results showed that Bali cattle are maintained in Unit Pelaksana Teknis (UPT) Pembibitan Sapi Bali, Sobangan, Badung has a good quality because it has a good body dimensions such as average the body lenght were 118,330±6,569- 123,970±5,305 cm, chest circumference chest circumference were 160,740±12,946- 174,060±10,361 cm,  estimated the body weight were 207,020±35,492 - 242,770±29,794 kg and body condition score (BCS) average of 3,500±0,683 - 3,700±0,560.
Keywords: body dimension, bali cattle, body weight, body condition score